2015
DOI: 10.1002/joc.4489
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the Standardized Precipitation Index for assessing inter‐annual rice yield variability in the Ganges–Brahmaputra–Meghna region

Abstract: Climate variability has major impacts on crop yields and food production in South Asia. The spatial differences of the impact are not, however, well understood. In this study, we thus aim to analyse the spatio-temporal relationship between precipitation and rice yields in the Ganges-Brahmaputra-Meghna region. The effects of rainfall variation on yields were analysed with regression models using the Standardized Precipitation Index (SPI) as an explanatory variable. Our results indicate that in large part of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 53 publications
2
14
0
Order By: Relevance
“…This index has many advantages such as simple calculation, good stability, multiple time scales, and space–time comparability. It has been widely used in drought monitoring 43,44 and can be used to accurately reflect the meteorological drought characteristics in Northwest China 45–48 . SPI assumes that changes in precipitation follow a gamma distribution and it uses mathematical methods to convert the cumulative frequency distribution of precipitation into a standard normal distribution.…”
Section: Methodsmentioning
confidence: 99%
“…This index has many advantages such as simple calculation, good stability, multiple time scales, and space–time comparability. It has been widely used in drought monitoring 43,44 and can be used to accurately reflect the meteorological drought characteristics in Northwest China 45–48 . SPI assumes that changes in precipitation follow a gamma distribution and it uses mathematical methods to convert the cumulative frequency distribution of precipitation into a standard normal distribution.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, when spring wheat yields were regressed against single water supply factor, precipitation during spring wheat growing season and soil water content in 50 cm depth, respectively, we found that the single factor could only explain as high as 30 variation of yield. However, in some studies, precipitation during growing season had significant relationship with crop yield Parthasarathy et al, 1988;Sneva, 1982 , and drought indices based on precipitation and other climatic factors during the crop growing period could precisely monitor agricultural drought Kattelus et al, 2016;Potopová et al, 2016;Yamoah et al, 2000 . The cause of the different results is that some crops have longer growing season, whereas others have shorter growing season.…”
Section: Discussionmentioning
confidence: 99%
“…For instance,calculation of 4-month timescale for April (named SPI-4-4) based on summation precipitation for January, February, March, and April. Computation of SPI using software of US National Drought Mitigation Center (US-NDMC) available at https://drought.unl.edu/droughtmonitoring/SPI/SPIProgram.aspx [15], [16].…”
Section: Standardized Precipitation Index (Spi)mentioning
confidence: 99%
“…Rice yield changes in time depend on several factors, such as weather factors, new management practices and technologies [15]. To capture the effect of weather factors, a linear time trend was removed from yield data and the proportional yield deviation (YD) calculated as follows:…”
Section: 4rice Yield (Qha -1 )mentioning
confidence: 99%